Fedora Linux toolbox : 1000+ commands for Fedora, CentOS, and Red Hat power users - Negus, Chris, 1957- (Wiley, 2008)
"In this handy, compact guide, you'll explore a ton of powerful Fedora Linux commands while you learn to use Fedora Linux as the experts do: from the command line. Try out more than 1,000 commands to find and get software, monitor system health and security, and access network resources. Then, apply the skills you learn from this book to use and administer desktops and servers running Fedora, CentOS, Red Hat Enterprise Linux, or any other Linux distribution"--Resource description page